Parkin Levels Decrease in Fibroblasts With Progranulin (PGRN) Pathogenic Variants and in a Cellular Model of PGRN Deficiency - Gaweda-Walerych, Katarzyna; Walerych, Dawid; Berdyński, Mariusz; Buratti, Emanuele; Zekanowski, Cezary (Frontiers in Molecular Neuroscience, 2021)
Frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS) are neurodegenerative diseases with TDP-43 mislocalization and aggregation. Genetic forms of FTLD and ALS are caused by mutations in various genes, such as PGRN (progranulin). Depletion of parkin RBR E3 ubiquitin protein ligase, a key mitophagy regulator, has been reported in sporadic ALS patients and ALS mice models with TDP-43 proteinopathy. In this work, we show parkin downregulation also in fibroblasts derived from FTLD patients with four different PGRN mutations. We corroborate this finding in control fibroblasts upon PGRN silencing, demonstrating additionally the decrease of parkin downstream targets, mitofusin 2 (MFN2) and voltage dependent anion channel 1 (VDAC1). Importantly, we show that TDP-43 overexpression rescues PRKN levels upon transient PGRN silencing, but not in FTLD fibroblasts with PGRN mutations, despite upregulating PGRN levels in both cases. Further observation of PRKN downregulation upon TDP-43 silencing, suggests that TDP-43 loss-of-function contributes to PRKN decrease. Our results provide further evidence that parkin downregulation might be a common and systemic phenomenon in neurodegenerative diseases with TDP- 43 loss-of-function.